The stability of perennial grasses mediates the negative impacts of long-term warming and increasing precipitation on community stability in a desert steppe - Lv, Guangyi; He, Mengting; Wang, Chengjie; Wang, Zhanyi (Frontiers in Plant Science, 2023)
Desert steppe, as an ecotone between desert and grassland, has few species and is sensitive to climate change. Climate change alters species diversity and the stability of functional groups, which may positively or negatively affect community stability. However, the response of plant community stability in the desert steppe to experimental warming and increasing precipitation remains largely unexplored. In a factorial experiment of warming and increasing precipitation for five to seven years (ambient precipitation (P0), ambient precipitation increased by 25% and 50% (P1 and P2), ambient temperature (W0), ambient temperature increased by 2℃ and 4℃ (W1 and W2)), we estimated the importance value (IV) of four functional groups (perennial grasses, semi-shrubs, perennial forbs and annual herbs), species diversity and community stability. Compared to W0P0, the IV of perennial grasses was reduced by 37.66% in W2P2, whereas the IV of perennial forbs increased by 48.96%. Although increasing precipitation and experimental warming significantly altered species composition, the effect on species diversity was insignificant (P > 0.05). In addition, increasing precipitation and experimental warming had a significant negative impact on community stability. The stability of perennial grasses significantly explained community stability. Our results suggest that the small number of species in desert steppe limits the contribution of species diversity to regulating community stability. By contrast, maintaining high stability of perennial grasses can improve community stability in the desert steppe.